The Women’s Movement and the struggle for land in Zimbabwe - Chingarande, Sunungurai (CLACSO, 2021)
Women in formalized (civil) and non-formalised (uncivil) groups have played a vital role in ensuring their improved access and control over land in Zimbabwe. Prior 1998, the involvement of women’s organizations and other civic groups in land issues was limited and marginal. During this time the women’s movement devoted its time and effort to welfare and development projects in communal areas. Emphasis by the more formal organisations was again on human rights and equality. Those that pursued land reform advocated for market-based and orderly methods of land reform, because the discourse at that time had shifted to radicalism. However, the market-based and orderly methods of land reform were gender blind. The aim at this time was to address racial imbalances, and gender imbalances were not foremost. Poor coordination of women’s organizations at this time affected efforts at addressing gender imbalances in land distribution. The ushering in of the Fast Track Land Reform Programme saw improved coordination of women’s organizations, that coincided with ‘uncivil’ women’s fight for land and land grabbing through the war veterans led land invasions that preceded the Fast Track period. Little has been done in terms of research to establish the role played by the uncivil women’s movement to the current land ownership pattern, but their role need not be underestimated. This paper mainly considers the role played by formalized or civil women’s movement to current achievements in women’s access and control of land under the Fast Track period. It specifically focuses on the role played by the Women and Land Lobby Group as well as other organizations in documenting the plight of women, lobbying for women’s access to land, advocating for legal reform in favour of women among other issues that facilitated improvements in women’s access to land under the Fast Track period.